Waqf as a means of forest conservation: alternative for Malaysia - Yaacob, Adzidah; Mahzir, Nurnadiah; Imam Supaat, Dina; Zakaria, Mohamad Zaharuddin; Wook, Izawati; Mustafa, Maizatun (American Scientific Publishers, 2017)
Forest of Peninsular Malaysia is a natural heritage that needs to be sustained for its uniqueness even though small in percentage, but it offers enormous benefits in safeguarding the natural ecosystem. Unfortunately, the state of deterioration of forested area in Peninsular Malaysia is at alarming rate and in need of additional funding instrument for conservation and regeneration. The Forest Development Fund established under Chapter 8 of the National Forestry Act 1984 has limited operation as its coverage only extends to existing forest conservation routine activities. Hence, this article seeks to highlight the preliminary research finding that is waqf shall be the alternative mechanism to protect and sustain the forest environment. Discussion in this article begins with the significance of forested area in the ecosystem and prolongs issues encircling the forest protection. It then explains financial and technical assistance available for forest conservation and the inadequacy to respond to current needs. Waqf has been implemented in several countries for the good of the community, thus it is seen as a potential tool to compliment efforts to preserve forest environment from depreciation. The role of the Islamic Religious Council as a sole trustee of all the waqf properties is also highlighted. Thus, this article proposed that by allocating specific land or any immovable assets in the name of waqf, the country could improve the state of forest that provides for water catchment areas, flood control mechanisms and also habitats for biodiversity. © 2017 American Scientific Publishers All rights reserved.